Early Mortality Rate in Patients Initiating Maintenance Hemodialysis in a Tertiary Care Hospital - Saleem, Mohammad; Rehan, Irtiqa; Rana, Mohammad Asim; Ahmad, Aftab; Asif, Maryam; Mehmood, Fahad; Qayyum, Mohammad Ahad (Pakistan Journal of Kidney Diseases, 2021)
This study was carried out to determine the early mortality rate i.e. 90 day mortality in patients starting maintenance hemodialysis at a tertiary care facility in Pakistan. This study additionally reports early mortality rate based on the type of vascular access used to initiate hemodialysis. Method: This is a cross sectional study which included all consecutive patients who initiated maintenance hemodialysis at Bahria Town International Hospital Lahore over a three-month period. Each patient was followed up for a period of 90 days and the type of vascular access used to initiate hemodialysis was noted. Early mortality rate i.e. 90-day mortality rate from the day of initiation of dialysis was calculated. All collected data was analyzed using the SPSS software. Results: A total of 485 participants were included in the study. The mean age was 44 years while 51% of the participants were male. The 90 day (early) mortality rate of patients initiating maintenance hemodialysis at our centre was found to be 45%. 88% of the patients initiated maintenance hemodialysis using a temporary hemodialysis catheter. 48% of the patients starting maintenance hemodialysis through a temporary dialysis catheter died within the 3 months of study period. Conclusion: The 90-day (early) mortality rate is significantly high i.e. 45% in patients initiating maintenance hemodialysis. The use of temporary hemodialysis catheter to initiate maintenance hemodialysis is a major risk factor for early mortality when compared to AVF use.